Art that explores history Reconceptualizing contemporary art's historicity in the global framework Review of: Eva Kernbauer, Art, History, and Anachronic Interventions Since 1990, New York City: Routledge, 2022. 260 pp., 53 colour ills, ISBN 9780367763251, Open Access, hbk £120.00. Issue 27 (2022) - Hopfener, Birgit
No abstract available